City of ghosts / 1. - Schwab, Victoria (Scholastic Press, 2018)
Ever since her near-fatal drowning, Cassidy has been able to pull back the "Veil" that separates the living from the dead and see ghosts, not that she wants to, and she was really looking forward to a ghost-free summer at the beach; however her parents are going to start filming a TV series about the world's most haunted places, starting with Edinburgh with its graveyards, castles, and restless phantoms--and Cass and her personal ghost companion, Jacob, are about to find out that a city of old ghosts can be a very dangerous place indeed.